2023
DOI: 10.1186/s12955-023-02097-y
|View full text |Cite
|
Sign up to set email alerts
|

Combining robot-assisted therapy with virtual reality or using it alone? A systematic review on health-related quality of life in neurological patients

Abstract: Background In the field of neurorehabilitation, robot-assisted therapy (RAT) and virtual reality (VR) have so far shown promising evidence on multiple motor and functional outcomes. The related effectiveness on patients’ health-related quality of life (HRQoL) has been investigated across neurological populations but still remains unclear. The present study aimed to systematically review the studies investigating the effects of RAT alone and with VR on HRQoL in patients with different neurologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 103 publications
1
12
0
Order By: Relevance
“…Investigating users' perceptions of neurorehabilitation is pivotal, as patients' motivation significantly predicts long-term changes in quality of life and rehabilitation outcomes [7]. Previous research confirmed that the combined use of conventional methods and technological devices could maximize rehabilitation effectiveness [60,[62][63][64]. Furthermore, our findings highlighted the satisfaction of patients with the multidisciplinary rehabilitation treatment and their active involvement in the recovery process.…”
Section: Motivation Patient Satisfaction Quality Of Lifesupporting
confidence: 58%
See 1 more Smart Citation
“…Investigating users' perceptions of neurorehabilitation is pivotal, as patients' motivation significantly predicts long-term changes in quality of life and rehabilitation outcomes [7]. Previous research confirmed that the combined use of conventional methods and technological devices could maximize rehabilitation effectiveness [60,[62][63][64]. Furthermore, our findings highlighted the satisfaction of patients with the multidisciplinary rehabilitation treatment and their active involvement in the recovery process.…”
Section: Motivation Patient Satisfaction Quality Of Lifesupporting
confidence: 58%
“…In line with these concerns, we have observed that the combined use of innovative rehabilitation with other interventions can contribute to a reduction in depressive symptoms. Indeed, the combination of robot-assisted therapy and VR has been shown to stand out as an innovative approach with substantial benefits for improving mood and alleviating depressive symptoms in patients with different neurological disorders [60]. While studies have traditionally focused on outcomes related to motor improvement and change in functional status, robotics and VR, alone or in combination, have shown a broader impact on the mental health and psychological well-being of individuals.…”
Section: Mood and Depressionmentioning
confidence: 99%
“…Zimmerli et al highlighted the pivotal role of interactivity (ie, functional feedback to motor performance) of VR in engaging patients in rehabilitation [86]. Other studies showcase the effectiveness of combining VR with other approaches, such as conventional physical therapy [34,36,59,61,70], robotic-assisted rehabilitation [11,67,83], and exoskeletons [26,41,76] in improving motor functions.…”
Section: Vr For Rehabilitationmentioning
confidence: 99%
“…Notably, Zanatta et al, 2023a , Zanatta et al, 2023b , Zanatta et al, 2022 ) explored the potential of combining robotic and virtual systems in rehabilitation, by analyzing their practical implications. The authors proposed a biopsychological approach to examine the points of view offered by multiple health-related perspectives, according to diverse technological solutions and heterogeneous conditions.…”
Section: Robotic and Vr Integration For Ms Rehabilitationmentioning
confidence: 99%